Dead Girl Running : Cape Charade #1 - Dodd, Christina (Don Mills, Ontario : HQN, 2018)
Surviving a gunshot wound to the head and missing memories from a year of her life, Kellan Adams finds herself on the run from a husband she hopes is dead and takes a job at a Pacific Coast resort, where she is embroiled in a murder investigation that makes her question her past.
Keywords: Amnesiacs -- Fiction; Murder -- Investigation -- Fiction; Amnesia -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; Suspense fiction